Hidup Bersama dengan Rukun untuk Membarui dalam Mazmur 133:1 (Menguatkan Penatalayanan Gereja dengan Kebersamaan dan Kerukunan Menuju Gereja yang Unggul Melayani) - Sukanto Limbong (CV. Creative Tugu Pena, 2024)
The Covid-19 pandemic has had a significant impact on church life and ministry to congregants, as outlined in the paper from the XXI GKPA Synod. This research aims to analyze the changes in conventional church growth indicators, such as attendance, building utilization, and finances, which are no longer effective benchmarks in these challenging times. Utilizing a qualitative approach and case study design, this study collects data through in-depth interviews, literature reviews, and participatory observations. The findings indicate that churches are required to adapt to the era of the Fourth Industrial Revolution while emphasizing the values of harmony highlighted in Psalm 133. Churches are called to